2015
DOI: 10.5336/ophthal.2015-44792
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anterior Segment Parameters Using Corneal Topography in Obstructive Sleep Apnea Syndrome

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Obstrüktif uyku apne sendromu (OUAS) olan hastaların ön segment parametrelerinin kornea topografisi ile değerlendirilmesi ve sağlıklı bireyler ile karşılaştırılmasıdır. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Bu prospektif çalışma kapsamında, 45 OUAS hastasının 45 gözü (OUAS grubu) ve 43 sağlıklı bireyin 43 gözü (kontrol grubu) değerlendirilmiştir. Tüm katılımcıların tanısı göğüs hastalıkları kliniği uyku laboratuvarında polisomnografi yapılarak konulmuştur. Hastaları… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Also, Hyon et al (2019) indicated that long-term computer use was possibly associated with an increased risk of DED. In addition, Bayhan et al (2014) reported that OSDI scores were significantly higher in the group using computers for a long time. Gajta et al (2015) concluded that VDT use for more than 8 h daily has been identified as a significant risk factor for dry eyes.…”
Section: Discussionmentioning
confidence: 98%
“…Also, Hyon et al (2019) indicated that long-term computer use was possibly associated with an increased risk of DED. In addition, Bayhan et al (2014) reported that OSDI scores were significantly higher in the group using computers for a long time. Gajta et al (2015) concluded that VDT use for more than 8 h daily has been identified as a significant risk factor for dry eyes.…”
Section: Discussionmentioning
confidence: 98%